Apical systolic click and murmur associated with neurofibromatosis. Issue 5 (October 1978) - Etches, P C; Pickering, D
Abstract : In this report we describe a child who had an apical systolic click and murmur, as well as widespread cutaneous neurofibromatosis. We were not able to show an anatomical basis for the click and murmur.